Definition of the dependence of QTc interval prolongation on glycemic control in patients with type 2 diabetes mellitus - Pertseva, N.O.; Moshenets, K.I. (Medicni Perspektivi, 2022)
The aim of the study: to assess the impact of glycemic variability on the duration of QTc interval in patients with diabetes mellitus type 2. 68 patients with type 2 diabetes mellitus (DM) and glycosylated hemoglobin (HbA1c) level ≤10% were examined. Of them – 37 (54.4%) men and 31 (45.6%) women. The average age – 46.0 (43.0; 54.0) years, the duration of DM type 2 – 7.0 (5.0; 9.0) years. Patients were divided into 2 groups according to HbA1c level: group 1 (n=31) with HbA1c <7% and group 2 (n=37) with HbA1c ≥7%. The control group consisted of 10 practically healthy people, compared by gender and age. The duration of the QTc interval was calculated automatically by Bazett’s formula during 24-hour Holter electrocardiogram (ECG) recordings. Additionally, the percentage of cases of exceeding the QTc threshold over 450 ms (QTc>450) was also calculated. Simultaneously with 24-hour Holter monitoring, the continuous glucose monitoring was performed, using iPro2 system (Medtronic MiniMed, USA). The maximum value of glycemia (Gmax), the minimum value of glycemia (Gmin), as well as indicators of glycemia variability (GV) were analyzed: standard deviation of mean glycemia (SD) and glycemia range (GR). The duration of daily QTc and the value of QTc >450 in patients with type 2 DM were significantly greater compared with the control group (p<0.05) and did not depend on the HbA1c level. In type 2 DM patients without recorded hypoglycemic episodes, the characteristics of QTc did not differ from the results of the control group (p>0.05). At the time of the hypoglycemic episode, the QTc duration in patients with type 2 DM significantly increased compared with the average daily value of QTc in the same patients – 487 (466; 519.5) ms against 436.5 (431; 452) ms (p<0.001). A strong correlation between QTc duration and the presence of hypoglycemia was determined (rs=0.78; p=0.023). QTc duration also correlated with GR (rs=0.23; p=0.016) and SD (rs=0.21; p=0.021). Therefore, it was found that in patients with type 2 diabetes, the prolongation of QTc duration is associated with high glycemic fluctuations and hypoglycemia (p<0.05) regardless of the HbA1c level.